(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In this work, a factor analysis of the structure of physical fitness of qualified handball players was conducted based on the study of physical qualities that directly affect the effectiveness of competitive activity. The main focus is on assessing speed qualities, special agility, endurance, strength, coordination, and flexibility, as these components are critically important for achieving high results in competitions. The results of the study are based on data from players of the Super League and the Higher League teams of the national championship of Ukraine, which allows us to take into account the specifics of training high-level professional handball players. The research process included the use of factor analysis to identify the main factors that determine the physical fitness of handball players. The work included measurements and evaluation of various physical qualities, including speed, endurance, explosive strength, coordination qualities, and flexibility. As a result of this analysis, it was possible to identify eight main factors that directly affect competitive activity in handball: speed qualities, special agility, speed endurance, explosive strength, power endurance, general performance, coordination qualities, and flexibility. This allowed us to create a clearer picture of the structural elements of physical fitness that must be optimized to achieve high results in competitions. First of all, the results of the study confirmed that the greatest influence on the competitive performance of handball players is exerted by speed qualities and special agility. This, in turn, confirms the conclusions made by Ukrainian and foreign researchers, who emphasize the critical importance of speed and agility for the successful execution of technical elements of the game. Speed and the ability to quickly change direction or perform complex technical elements are critical for high performance on the field. Research shows that a high level of speed allows players not only to perform complex maneuvers, but also to implement tactical ideas, which is an important aspect in modern handball, where speed of action is crucial.